Kontrol Diri dan Tekanan Teman Sebaya (Peer Pressure) dengan Kenakalan Remaja pada Kalangan Remaja Kelurahan Klender - Nathaline, Grace; J. Silaen, Sondang Maria (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This research is a quantitative study which aims to examine the relation between selfcontrol and negative peer pressure with juvenile delinquency among adolecents of KelurahanKlender. The subjects in this study were 64 adolescents as a sample with the method of datacollection using multistage random sampling techniques. Measuring instruments used werejuvenile delinquency scale, self-control scale, and negative peer pressure scale. The resultsshowed that there was a significant negative relation between self-control and juveniledelinquency for -0756, and there was a significant positive relation between negative peerpressure and juvenile delinquency for 0,815. Furthermore, the results of data analysis withmultivariate correlation using the SPSS (Statistical Product and Service Solution) computerprogram version 26.0 for windows obtained the correlation coefficient R = 0,829. From theresults of this study it can be concluded that the lower self-control, the higher juveniledelinquenc, and then, the higher negative peer pressure, the higher juvenile delinquency.Keywords : Juvenile Delinquency, Self-Control, Negative Peer Pressure.